Energy saving on campus: a comparison of students' attitudes and reported behaviours in the UK and Portugal. (15th August 2016) - Cotton, Debby; Shiel, Chris; Paço, Arminda
Abstract: Energy saving on campus is an increasingly important part of universities' responses to climate change, but can only be fully realised through a partnership between institutions and students. This study explores similarities and differences between students' energy-related attitudes and reported behaviours, as well as their perceptions of their institution's energy saving efforts using data from two universities in the United Kingdom (UK) and one in Portugal. The results indicate that there are differences between the students' responses at the selected universities which appear to reflect the national context and diverse institutional priorities. Key differences include the variation between students' perceptions of individual agency and their university's environmental practices (stronger in the UK) and students' sense of collective agency and trust in the government and business (stronger in Portugal). The study is the first to attempt a comparison between students from institutions in different countries in relation to energy saving. It provides a foundation to extend the comparison to other institutions and other countries, and to expand the research to encompass actual energy use, in relation to perceived energy use. Highlights: This research explores similarities and differences between students' energy-related attitudes and reported behaviours. It also involves an analysis of students' views on three universities' energy saving efforts, in two European countries. Differences between the students' responses appear to reflect the national context and the institutional priorities.